2010
DOI: 10.1159/000321465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychiatric Severity on the Outcome of Methadone Maintenance Treatment

Abstract: While psychiatric comorbidity has been shown to produce a negative impact on the outcome of opioid use disorders, longitudinal studies carried out in the context of methadone maintenance treatment programs (MMTP) to evaluate outcomes strictly linked to methadone efficacy have not demonstrated a similar negative influence. To verify whether results obtained considering psychopathology in terms of formal psychiatric diagnoses were replicated when assessing psychopathology in terms of global psychiatric severity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 104 publications
(65 reference statements)
4
25
0
1
Order By: Relevance
“…Therefore, inflammatory processes may have influenced the serum levels of both growth factors investigated in this study, which we did not control. Moreover, as is typical for opiate-dependent patients treated with DAM [28,29], patients enrolled in this study were not only treated with DAM but also with further substances like methadone or antidepressants. Urine samples revealed that the patients also consumed further psychotrophic substances like benzodiazepines and amphetamines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammatory processes may have influenced the serum levels of both growth factors investigated in this study, which we did not control. Moreover, as is typical for opiate-dependent patients treated with DAM [28,29], patients enrolled in this study were not only treated with DAM but also with further substances like methadone or antidepressants. Urine samples revealed that the patients also consumed further psychotrophic substances like benzodiazepines and amphetamines.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study, severity of psychiatric comorbidity was not shown to be associated with lower retention in treatment or higher substance use during treatment [28]. The influence of mental disorders on acute somatic morbidity would have been of interest, but these data were not available in this study.…”
Section: Discussionmentioning
confidence: 82%
“…La prevalencia de comorbilidad psiquiátrica entre los sujetos dependientes de opiáceos que acuden a tratamiento varía entre 44% y 93%, siendo los trastornos depresivos y de ansiedad y los trastornos de personalidad antisocial y límite los más frecuentes (Mateu, Astals y Torrens, 2005). Un estudio reciente, señala como aquellos pacientes con trastornos psiquiátricos más graves mejoran significativamente en las dimensiones psicológicas y psiquiátricas del SCL-90 durante el tratamiento con metadona (Pani et al, 2011).…”
Section: Marcadores De Salud Física Y Mental En Tmmunclassified